Transfiguratus est ante eos. Desarrollo teológico de la Transfiguración del Señor en un sermón inédito del siglo XVIII (2020)
In the Historical Archive of the Province of San Luis Bertrán-Colombia (AHPSBC), there are several sermons preached by the Dominican friars of New Granada during the 18th century. Based on the historical-critical and theological methods, a theological analysis of the Transfiguration sermon is made here: Transfiguratus est ante eos (Mat 17, 2), preached on August 6, 1786; through an identification of theological categories based on biblical and patristic sources, as well as the other ecclesiastical writers proposed by the author. Due to all the iconic and apologetic language that these texts have, contributions to the History of Theology are provided through the palaeographic, archival, diplomatic and codicological analysis of the document.